2010
DOI: 10.1519/jsc.0b013e3181e27386
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the 1RM Estimation Method Based on Isometric Squat Using A Back-Dynamometer

Abstract: This study aimed to clarify the relationships between isometric squat (IS) using a back dynamometer and 1 repetition maximum (1RM) squat for maximum force and muscle activities and to examine the effectiveness of a 1RM estimation method based on IS. The subjects were 15 young men with weight training experience (mean age 20.7 ± 0.8 years, mean height 171.3 ± 4.4 cm, mean weight 64.4 ± 8.4 kg). They performed the IS with various stance widths and squat depths. The measured data of exerted maximum force and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
2
14
1
3
Order By: Relevance
“…Other covariates, including age, resistance training history, and BMI, were not shown to contribute to the prediction equations. The current study found greater accuracies in the 1RM prediction equations derived from isometric strength assessments (standard error of estimate: biceps ¼ 2.5 kg, quadriceps ¼ 7.5 kg), as compared to previous studies by Blazevich (standard error of estimate: 1RM squat ¼ 11.9 kg) and Demura (standard error of estimate: 1RM squat ¼ 13.8 kg) who compared isometric versus 1RM squats [37,38]. The choice of a single joint movement for strength assessments in this study could have contributed to the increased accuracies in the 1RM prediction equations, as standardization of a compound exercise (ie, squat) during strength assessment is difficult.…”
Section: Discussioncontrasting
confidence: 53%
“…Other covariates, including age, resistance training history, and BMI, were not shown to contribute to the prediction equations. The current study found greater accuracies in the 1RM prediction equations derived from isometric strength assessments (standard error of estimate: biceps ¼ 2.5 kg, quadriceps ¼ 7.5 kg), as compared to previous studies by Blazevich (standard error of estimate: 1RM squat ¼ 11.9 kg) and Demura (standard error of estimate: 1RM squat ¼ 13.8 kg) who compared isometric versus 1RM squats [37,38]. The choice of a single joint movement for strength assessments in this study could have contributed to the increased accuracies in the 1RM prediction equations, as standardization of a compound exercise (ie, squat) during strength assessment is difficult.…”
Section: Discussioncontrasting
confidence: 53%
“…This finding is comparable to others (45-55%) who have employed similar joint angle constraints during 1RM back squat [6] and isometric horizontal leg press assessment [21]. Differences in force output are attributable to changes in the muscle length-tension relationship and the alteration of muscle moment arm length imposed by the body segment orientation [22]. Intuitively, one might expect ISO90 to have a greater force generating capacity than ISO120 given the length-tension relationship of the knee flexors; however, multijoint exercises such as the leg press incorporate numerous muscle groups (gluteal and triceps surae, for example) that also contribute force production.…”
Section: Discussionsupporting
confidence: 86%
“…This widened stance width enhances the mean electromyography value of the gluteus maximus during a squat [ 12 14 ]. The stance width at the set position of the block start has been reported to be 23 ± 1 cm [ 15 ]; this is shorter than the stance width in previous studies on widened stance width in squatting [ 11 14 ]. These studies may indicate that a widened stance width during the block start phase would enhance block-induced power during the block start phase attained by a greater hip joint power.…”
Section: Introductionmentioning
confidence: 95%
“…This leg extension motion during the block start phase is similar to the double-legged squat motion [ 10 ]. Biomechanical analysis of the squatting motion has revealed that lengthening the mediolateral distance between feet (140% of shoulder width) contributes to stronger isometric contractions in lower limb muscles [ 11 ]. This widened stance width enhances the mean electromyography value of the gluteus maximus during a squat [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%